Kinetic-Spectrophotometric Studies on Periodate Oxidation of 2-Amino-p-Xylene in Acetone-Water Medium - Kaushik, R.D.; Sundriyal, Purnima; Kumar, Tarun; Singh, Prabha (Asian Journal of Chemistry, 2010)
The results of kinetic-mechanistic study on the periodate oxidation of 2-amino-p-xylene (XYL) have been presented and discussed. The reaction has been followed by monitoring the increase in the absorbance of reaction mixture spectrophotometrically. The reaction followed second order behaviour, being first order in each reactant. The rate of reaction decreases with decrease in dielectric constant of the medium. Free radical scavengers do not affect the reaction rate. A positive effect of ionic strength on rate is observed. The stoichiometry has been found to be 1 mol XYL: 2 mol of periodate. Thermodynamic parameters evaluated are: Ea = 7.3 kcal mol-1, A = 9001 dm3 mol-1 s-1; ΔS# = - 43.7 cal mol-1, ΔG# = 20.4 kcal mol-1 and ΔH# = 6.6 kcal mol-1. The rate law, under pseudo first order conditions, [IO4 – ] >> [XYL], is given by, d[C]/dt = kK [IO4 – ]0[S] / (1+K[IO4 – ]0). Likewise, under the conditions, [XYL] >> [IO4 – ], it is: d[C]/dt = kK [IO4– ] [S]0 / (1+K[S]0). The complete rate law including the [H+] dependence under the conditions, [IO4 – ] >> [XYL], is given by: d[C]/dt = kKKw [S] [IO4 – ]0 [H+]/K2 Kw + (Kw + Kb K2) [H+] + Kb [H+]2where kK is the empirical composite rate constant, Kw is ionic product of water, K2 is acid dissociation constant of H4IO6 –, Kb is base dissociation constant of XYL. [S] is the concentration of XYL and [IO4 – ]0 represents the concentration of periodate that has been taken in excess. The value of [H+] at which minima is obtained in the 1/k2 - [H+] profile, is in excellent agreement with that calculated from the derived rate law. Main reaction product isolated and characterized is 2,5-dimethyl-1,4-benzoquinone.